Degradation of the cyanotoxin microcystin-LR using iron-based photocatalysts under visible light illumination - Han, Changseok; Machala, Libor; Medrik, Ivo; Prucek, Robert; Kralchevska, Radina P; Dionysiou, Dionysios D (Environmental science and pollution research international, 2017)
In this study, a simple and low-cost method to synthesize iron(III) oxide nanopowders in large quantity was successfully developed for the photocatalytic degradation of microcystin-LR (MC-LR). Two visible light-active iron(III) oxide samples (MG-9 calcined at 200 °C for 5 h and MG-11 calcined at 180 °C for 16 h) with a particle size of 5-20 nm were prepared via thermal decomposition of ferrous oxalate dihydrate in air without any other modifications such as doping. The synthesized samples were characterized by X-ray powder diffraction, 57Fe Mössbauer spectroscopy, transmission electron microscopy, Brunauer-Emmett-Teller (BET) specific surface area analysis, and UV-visible diffuse reflectance spectroscopy. The samples exhibited similar phase composition (a mixture of α-Fe2O3 and γ-Fe2O3), particle size distribution (5-20 nm), particle morphology, and degree of agglomeration, but different specific surface areas (234 m2 g-1 for MG-9 and 207 m2 g-1 for MG-11). The results confirmed higher photocatalytic activity of the catalyst with higher specific surface area. The highest photocatalytic activity of the sample to decompose MC-LR was observed at solution pH of 3.0 and catalyst loading of 0.5 g L-1 due to large amount of MC-LR adsorption, but a little iron dissolution of 0.0065 wt% was observed. However, no iron leaching was observed at pH 5.8 even though the overall MC-LR removal was slightly lower than at pH 3.0. Thus, the pH 5.8 could be an appropriate operating condition for the catalyst to avoid problems of iron contamination by the catalyst. Moreover, magnetic behavior of γ-Fe2O3 gives a possibility for an easy separation of the catalyst particles after their use.
Keywords: Iron oxide; Water treatment; povrchové vlastnosti; Catalysis; světlo; Mössbauer spectroscopy; Microcystin; mikrocystiny; Marine Toxins; mořské toxiny; velikost částic; Light; Ferric Compounds; Adsorption; Carcinogens; Hydrogen-Ion Concentration; karcinogeny; železité sloučeniny; magnetické nanočástice; adsorpce; Microcystins; koncentrace vodíkových iontů; Particle Size; Magnetite Nanoparticles; katalýza; Surface Properties; Photocatalysis